2023
DOI: 10.3390/molecules28073149
|View full text |Cite
|
Sign up to set email alerts
|

Papaverine: A Miraculous Alkaloid from Opium and Its Multimedicinal Application

Abstract: The pharmacological actions of benzylisoquinoline alkaloids are quite substantial, and have recently attracted much attention. One of the principle benzylisoquinoline alkaloids has been found in the unripe seed capsules of Papaver somniferum L. Although it lacks analgesic effects and is unrelated to the compounds in the morphine class, it is a peripheral vasodilator and has a direct effect on vessels. It is reported to inhibit the cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Although the in vivo effects of papaverine have not been fully elucidated, it is known to increase cAMP (cyclic adenosine monophosphate) and cGMP (cyclic guanosine monophosphate) levels through the inhibition of phosphodiesterase enzymes. [ 23 ] These intracellular secondary messengers play pivotal roles in transmitting various physiological stimuli and regulating numerous physiological processes, including vascular resistance, cardiac output, visceral motility, immune responses, inflammation, neuroplasticity, vision, and reproduction. [ 24 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the in vivo effects of papaverine have not been fully elucidated, it is known to increase cAMP (cyclic adenosine monophosphate) and cGMP (cyclic guanosine monophosphate) levels through the inhibition of phosphodiesterase enzymes. [ 23 ] These intracellular secondary messengers play pivotal roles in transmitting various physiological stimuli and regulating numerous physiological processes, including vascular resistance, cardiac output, visceral motility, immune responses, inflammation, neuroplasticity, vision, and reproduction. [ 24 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Papaverine is also widely used in urology for diagnosing and treating impotence. [ 23 ] Interestingly, a study evaluating the effects of sildenafil, another phosphodiesterase inhibitor used in impotence treatment, on Achilles tendon healing reported positive histopathological effects. [ 32 ] In our study, while biomechanical effects were evident in the late period, positive differences were observed in all groups receiving papaverine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the alkaloids detected in PBP extracts can actually exert beneficial effects for humans through consumption. For instance, isoquinoline alkaloids possess anticancer properties [50], while papaverine, per se, has been recognized as a miracle compound with different health benefits [51]. It has been demonstrated that local application of papaverine on patients with end-stage renal disease can induce a reduction in arteriovenous fistula maturation without any additional difficulties [52].…”
Section: Uhplc Alkaloid Profile Of Pbpmentioning
confidence: 99%